Integration of Web-Based and Mobile Application with QR Code implementation for the library management system - Din M.M.; Fazal Fazla A. (IOP Publishing Ltd, 2023)
Acceptance tests; Bar codes; Digital devices; Information dissemination; Electronic device; Higher learning institutions; Library management; Library systems; Mobile applications; Physical locations; Quick response code; Two-dimensional bar codes; Search engines